Sexual Health Influencer Distribution of HIV/Syphilis Self-Tests Among Men Who Have Sex With Men in China: Secondary Analysis to Inform Community-Based Interventions - Yang, Nancy; Wu, Dan; Zhou, Yi; Huang, Shanzi; He, Xi; Tucker, Joseph; Li, Xiaofeng; Smith, Kumi M; Jiang, Xiaohui; Wang, Yehua; Huang, Wenting; Fu, Hongyun; et al. (JMIR Publications, 2021)
BackgroundSocial network-based strategies can expand HIV/syphilis self-tests among men who have sex with men (MSM). Sexual health influencers are individuals who are particularly capable of spreading information about HIV and other sexually transmitted infections (STIs) within their social networks. However, it remains unknown whether a sexual health influencer can encourage their peers to self-test for HIV/syphilis. ObjectiveThe aims of this study were to examine the impact of MSM sexual health influencers on improving HIV/syphilis self-test uptake within their social networks compared to that of nonsexual health influencers. MethodsIn Zhuhai, China, men 16 years or older, born biologically male, who reported ever having had sex with a man, and applying for HIV/syphilis self-tests were enrolled online as indexes and encouraged to distribute self-tests to individuals (alters) in their social network. Indexes scoring >3 on a sexual health influencer scale were considered to be sexual health influencers (Cronbach α=.87). The primary outcome was the mean number of alters encouraged to test per index for sexual health influencers compared with the number encouraged by noninfluencers. ResultsParticipants included 371 indexes and 278 alters. Among indexes, 77 (20.8%) were sexual health influencers and 294 (79.2%) were noninfluencers. On average, each sexual health influencer successfully encouraged 1.66 alters to self-test compared to 0.51 alters encouraged by each noninfluencer (adjusted rate ratio 2.07, 95% CI 1.59-2.69). More sexual health influencers disclosed their sexual orientation (80.5% vs 67.3%, P=.02) and were community-based organization volunteers (18.2% vs 2.7%, P<.001) than noninfluencers. More alters of sexual health influencers came from a rural area (45.5% vs 23.8%, P<.001), had below-college education (57.7% vs 37.1%, P<.001), and had multiple casual male sexual partners in the past 6 months (25.2% vs 11.9%, P<.001). ConclusionsBeing a sexual health influencer was associated with encouraging more alters with less testing access to self-test for HIV/syphilis. Sexual health influencers can be engaged as seeds to expand HIV/syphilis testing coverage.